Community Empowerment in Stunting Prevention through Smart Parenting - Suryani , Putri Salsabila; Nurhidayah, Siti; Basri, Hasan; Putrianika, Puput (Santoso Academy Network, 2024)
Stunting is a chronic malnutrition problem caused by insufficient nutritional intake for a long time due to feeding that is not in accordance with nutritional needs. Stunting can occur from the time the fetus is still in the womb and only appears when the child is two years old and if it is not offset by declining growth. The problem of stunting is a public health problem associated with an increased risk of morbidity, mortality, and obstacles to growth, both motor and mental. The implementation method that will be carried out is the community education method through community seminars. The seminar method is carried out to conduct counseling for Sukabungah Village residents about stunting prevention. The seminars and socialization that have been carried out by the service team in Sukabungah Village provide new insights and knowledge to the local community about the importance of preventing stunting by providing adequate nutrition and nutrition to infants and pregnant women as well as knowledge of the mental readiness of prospective parents to become parents. Thus, the socialization of stunting prevention provides a small movement for the impact of positive changes on stunting prevention through optimizing the role of parents as smart parenting.